Biosensors with Boronic Acid-Based Materials as the Recognition Elements and Signal Labels - Lin Liu; Xiaohua Ma; Yong Chang; Hang Guo; Wenqing Wang (Biosensors, 2023)
It is of great importance to have sensitive and accurate detection of cis-diol-containing biologically related substances because of their important functions in the research fields of metabolomics, glycomics, and proteomics. Boronic acids can specifically and reversibly interact with 1,2- or 1,3-diols to form five or six cyclic esters. Based on this unique property, boronic acid-based materials have been used as synthetic receptors for the specific recognition and detection of cis-diol-containing species. This review critically summarizes the recent advances with boronic acid-based materials as recognition elements and signal labels for the detection of cis-diol-containing biological species, including ribonucleic acids, glycans, glycoproteins, bacteria, exosomes, and tumor cells. We also address the challenges and future perspectives for developing versatile boronic acid-based materials with various promising applications.